Comparative Ecology of Bartonella and Brucella Infections in Wild Carnivores - Kosoy, Michael; Goodrich, Irina (Frontiers in Veterinary Science, 2019)
Phylogenetic sister clades Bartonella and Brucella within the order Rhizobiales present some common biological characteristics as well as evident differences in adaptations to their mammalian reservoirs. We reviewed published data on Bartonella and Brucella infections in wild carnivores to compare the ecology of these bacteria in relatively similar host environments. Arthropod vectors are the main mechanism for Bartonella species transmission between mammalian hosts. The role of arthropods in transmission of Brucella remains disputed, however experimental studies and reported detection of Brucella in arthropods indicate potential vector transmission. More commonly, transmission of Brucella occurs via contact exposure to infected animals or the environment contaminated with their discharges. Of 26 species of carnivores tested for both Bartonella and Brucella, 58% harbored either. Among them were bobcats, African lions, golden jackals, coyotes, wolves, foxes, striped skunks, sea otters, raccoons, and harbor seals. The most common species of Bartonella in wild carnivores was B. henselae, found in 23 species, followed by B. rochalimae in 12, B. clarridgeiae in ten, and B. vinsonii subsp. berkhoffii in seven. Among Brucella species, Br. abortus was reported in over 30 terrestrial carnivore species, followed by Br. canis in seven. Marine carnivores, such as seals and sea lions, can host Br. pinnipedialis. In contrast, there is no evidence of a Bartonella strain specific for marine mammals. Bartonella species are present practically in every sampled species of wild felids, but of 14 Brucella studies of felids, only five reported Brucella and those were limited to detection of antibodies. We found no reports of Bartonella in bears while Brucella was detected in these animals. There is evident host-specificity of Bartonella species in wild carnivores (e.g. B. henselae in felids and B. vinsonii subsp. berkhoffii in canids). A co-adaptation of Brucella with terrestrial wild carnivore hosts is not as straightforward as in domestic animals. Wild carnivores often carry the same pathogens as their domesticated relatives (cats and dogs), but the risk of exposure varies widely because of differences in biology, distribution, and historical interactions.